2021
DOI: 10.1096/fasebj.2021.35.s1.03946
|View full text |Cite
|
Sign up to set email alerts
|

Circulating NGF is correlated with indexes of diabetes progression and P2X 3 expression in UCD‐T2DM rats

Abstract: Type 2 diabetes is associated with neuropathic symptoms, including development of peripheral neuropathy and an exaggerated exercise pressor reflex, both of which have been demonstrated in UC Davis Type 2 diabetes mellitus (UCD‐T2DM) rats. This novel animal model more closely mimics the human disease state than traditional T2DM rodent models. Several studies have demonstrated changes in nerve growth factor (NGF) in diabetic patients, with some showing increases and others decreases, and this has been proposed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“… 36 Animal studies have shown that lowering NGF levels leads to increased blood sugar and insulin resistance in diabetes. 37 One study found that elevated plasma NGF levels in patients with MetS were considerably higher than in normal individuals. 10 It has been suggested that NGF can be involved in cellular function by initiating phosphorylation of the protein cascade.…”
Section: Discussionmentioning
confidence: 99%
“… 36 Animal studies have shown that lowering NGF levels leads to increased blood sugar and insulin resistance in diabetes. 37 One study found that elevated plasma NGF levels in patients with MetS were considerably higher than in normal individuals. 10 It has been suggested that NGF can be involved in cellular function by initiating phosphorylation of the protein cascade.…”
Section: Discussionmentioning
confidence: 99%